2022
DOI: 10.1080/2162402x.2022.2068109
|View full text |Cite
|
Sign up to set email alerts
|

Conventional amphotericin B elicits markers of immunogenic cell death on leukemic blasts, mediates immunostimulatory effects on phagocytic cells, and synergizes with PD-L1 blockade

Abstract: Immunostimulatory regimens are a game changer in the fight against cancer, but still only a minority of patients achieve clinical benefit. Combination with immunomodulatory drugs and agents converting otherwise non-immunogenic forms of cell death into bona fide “immunogenic cell death” (ICD) could improve the efficacy of these novel therapies. The aim of our study was to investigate conventional Amphotericin B (AmB) as an enhancer of antitumor immune responses. In tumor cell line models, AmB induced ICD with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The prototypic ICD-associated “eat-me” signal is CALR, an endoplasmic reticulum (ER) chaperone that is exposed on the outer leaflet of the plasma membrane downstream of the integrated stress response (ISR) and consequent phosphorylation of eukaryotic translation initiation factor 2 subunit alpha (EIF2S1, best known as eIF2α) [ 47 , 48 ]. Common immunostimulatory DAMPs mechanistically linked to ICD encompass ATP, which is actively secreted by an autophagy-dependent mechanism [ 49 ], as well as high mobility group box 1 (HMGB1) and annexin A1, both of which appear to be passively released upon nuclear and plasma membrane permeabilization [ 50 52 ]. Finally, type I interferon (IFN) and C-X-C motif chemokine ligand 10 (CXCL10) have been involved in multiple instances of ICD [ 53 , 54 ].…”
Section: Core Icd Determinantsmentioning
confidence: 99%
“…The prototypic ICD-associated “eat-me” signal is CALR, an endoplasmic reticulum (ER) chaperone that is exposed on the outer leaflet of the plasma membrane downstream of the integrated stress response (ISR) and consequent phosphorylation of eukaryotic translation initiation factor 2 subunit alpha (EIF2S1, best known as eIF2α) [ 47 , 48 ]. Common immunostimulatory DAMPs mechanistically linked to ICD encompass ATP, which is actively secreted by an autophagy-dependent mechanism [ 49 ], as well as high mobility group box 1 (HMGB1) and annexin A1, both of which appear to be passively released upon nuclear and plasma membrane permeabilization [ 50 52 ]. Finally, type I interferon (IFN) and C-X-C motif chemokine ligand 10 (CXCL10) have been involved in multiple instances of ICD [ 53 , 54 ].…”
Section: Core Icd Determinantsmentioning
confidence: 99%
“…In our study, electrochemotherapy with all three tested chemotherapeutics induced ICD-associated DAMPs, but the induced DAMP signature was cell line and chemotherapeutic concentration specific. Some ICD-triggering regimens may also boost antigenicity through the modification of cell surface marker expression [ 25 , 34 , 37 , 38 ]. In our study, we showed that electrochemotherapy with CDDP, OXA or BLM can modify the expression of MHC I, MHC II, PD-L1 and CD40 cell surface markers.…”
Section: Discussionmentioning
confidence: 99%
“…Besides DAMPs, chemotherapeutics can also help upregulate antigen presentation and decrease tumor immune escape [ 25 , 36 ]. It was already shown that in some cancers CDDP can upregulate MHC I and PD-L1; OXA can upregulate MHC I and PD-L1; and BLM can upregulate PD-L1 [ 34 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, photothermal therapy and the CDT-mediated ICD improve anti-tumor immunity by exposing HMGB1, CRT, and ATP. Reports also suggest Amphotericin B (AmB) enhances the anti-tumor immune response by releasing HMGB1, which induces ICD ( 29 ). Studies show a correlation between high serum concentration of IL-33 and inflammation, poor prognosis, and severity of aSAH.…”
Section: Discussionmentioning
confidence: 99%